PENERAPAN TEKNIK MARMET UNTUK MENINGKATKAN PRODUKSI ASI PADA IBU POST PARTUM DI RUMAH SAKIT TK III 04.06.02 BHAKTI WIRA TAMTAMA SEMARANG : APPLICATION OF MARMET TECHNIQUE TO INCREASE THE PRODUCTION OF BREAST MILK IN POST PARTUM MOTHER AT HOSPITAL TK III 04.06.02 BHAKTI WIRA TAMTAMA SEMARANG - Vidiya Arum Miftachul Jannah; Yuni Astuti (JURNAL KEPERAWATAN SISTHANA, 2019)
Breast milk is the best food for babies, because breast milk contains nutrients and all the nutrients with the amount and composition needed by the baby. one of the obstacles in the process of lactation on the first day is the mother does not produce enough breast milk or the baby does not want to suck so that the mother does not want to breastfeed the baby. Way that can be done to increase milk production is by doing the technique marmet. This case study aims to illustrate the increased production breast milk in post partum mothers after nursing with marine techniques in hospitals Bougenville Room TK III 04.06.02 Bhakti Wira Tamtama Semarang. The type of this research is descriptive by using case study approach method. Subjects in this study were two patients with postpartum mother with criteria of primiparous mother, postpartum mother who breastfeeding, mother who is willing to be respoden, babies performed nursing. The analysis was measured based on an observed sheet of fluid milk production. the results of case studies show an increase in milk production from a score of 12 categories not smooth to score 19 categories smoothly on subject I and score 13 categories not smooth to score 20 categories smoothly on subject II. Recommendations need to be consistent nurses in taking action marmet techniques to increase milk production in primipara mother.